Expanding the concept of serotoninomics: perspectives for serotonin studies in the 20’s of the 21st century - Jiménez-Trejo, Francisco; Tapia-Rodríguez, Miguel; Arriaga-Canon, Cristian; Herrera, Luis A.; Contreras-Espinosa, Laura; Jiménez-García, Katia Lorena (Frontiers in Neuroscience, 2023)
Surely, Vittorio Erspamer, discoverer of Enteramine in 1935, and Irvine Page, Maurice M.Rapport and Arda Green, discoverers of Serotonin in 1948, never imagined the biological importance that this fundamental molecule has in the living beings of our planet; from its physiological, passing through endocrine, neural, developmental and reproductive functions and even its role in evolution. For this reason, our workgroup wants to commemorate these researchers and celebrate their great discovery, which deeply influenced science and medicine. As a consequence of their seminal work, and the work of many other researchers in the field of serotonin over the following years, now we stand in front of the practical concept of "Serotoninomics", which we think will contribute to find out precise answers regarding basic, clinical, and translational research related to serotonin, just as the emerging medical and "omics" sciences have done before.